Kualitas Pelayanan Terhadap Peningkatan Kepuasan Pelanggan pada PT. Pos Indonesia Kota Kendari - Anawai, Sisca; Gunawan, Gunawan; Liwaul, Liwaul (REZ PUBLICA, 2021)
This study aims to determine the quality of service to increase customer satisfaction at PT. Pos Indonesia Kendari City. The type of research used in this research is descriptive and causal research with a quantitative approach. The sampling technique used is non-probability using a sample of 30 respondents. While the data analysis technique used is the descriptive analysis technique.Â The results showed that the quality of service at the office of PT. Pos Indonesia Kendari City has reached the very good category in the dimensions of responsiveness, assurance, empathy, and physical evidence. While the reliability dimension reaches a good category. On the customer satisfaction variable, the results of the study show that the suitability of service quality with the level of expectations has reached a good category, while customer satisfaction has reached a fairly good category on the satisfaction level indicator when compared to similar ones and there are no complaints or complaints. the complaint that was filed.